2013
DOI: 10.5539/jas.v6n1p123
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Assessment of Some Plants Latex as Biopesticide Against Cowpea Bruchid, Callosobruchus maculatus (Fab.) [Coleoptera: Chrysomelidae]

Abstract: Laboratory evaluation of Calotropis procera, Alstonia boonei, Jatropha curcas and Argemone mexicana latex as biopesticide against cowpea bruchid, Callosobruchus maculatus (Fab.) [Coleoptera: Chrysomelidae] were evaluated at ambient temperature and relative humidity of 28±2 o C and 75±5% respectively. The plants latex was tested at rates of 0.5 ml, 1 ml, 1.5 ml and 2 ml / 20 g of cowpea seeds. Adult mortality and adult emergence of the insects were investigated. Results showed that at rates of 1 ml, 1.5 ml and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The insecticidal activity of A. boonei has been reported recently (Oigiangbe et al, 2007a;2007b;Ileke and Oni 2011;Ileke et al, 2012;Ileke et al, 2013;2014;Ojo and Ogunleye, 2013). Aqueous extracts of the leaf and stem bark of A. boonei was active against the pink borer, Sesamia calamistis Hampson (Lepidoptera: Noctuidae), a pest of maize and some other cereals in West and Central Africa (Oigiangbe et al, 2007a).…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…The insecticidal activity of A. boonei has been reported recently (Oigiangbe et al, 2007a;2007b;Ileke and Oni 2011;Ileke et al, 2012;Ileke et al, 2013;2014;Ojo and Ogunleye, 2013). Aqueous extracts of the leaf and stem bark of A. boonei was active against the pink borer, Sesamia calamistis Hampson (Lepidoptera: Noctuidae), a pest of maize and some other cereals in West and Central Africa (Oigiangbe et al, 2007a).…”
Section: Introductionmentioning
confidence: 70%
“…Previous studies by Oigiangbe et al (2007a;2007b); Ileke and Oni (2011), Ileke et al (2012); ; Ileke et al (2013;2014) and Ojo and Ogunleye (2013) have shown insecticidal activity of A. boonei powders and A. boonei extracts on the pink borer, Sesamia calamistis Hampson (Lepidoptera: Noctuidae) a pest of maize and some other cereals, Maruca vitrata (Lepidoptera: Pyralidae), cowpea bruchid C. maculatus (Coleoptera: Chrysomelidae), mosquito larvae and S . zeamais (Coleoptera: Curculionidae) respectively.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies by Ileke and Oni (2011);Ileke et al (2012); Ileke et al (2013); Ileke et al (2014) have shown insecticidal activity of A. boonei powders against Sitophilus zeamais, A. boonei stem bark oil obtained by cold extraction using five different solvents on the mortality of cowpea bruchid, C. maculatus and A. boonei latex against C. maculatus. In this study, A. boonei stem bark extract was the most toxic to adult C. maculatus.…”
Section: Discussionmentioning
confidence: 86%
“…Deterrent effects on F 1 progeny that emerged into adults affected the postembryonic development that performed in less or even completely no adult emergence. This might have been caused by the VOCs from plant powders which poses the ability to penetrate the eggs chorion of insect through a minute space (micropyle) that is present on the posterior pole of eggs and results in the death of embryos and/or neonate larvae (Ileke et al, 2014;Kedia et al, 2015;Zafar et al, 2018). At the end of the experiment, little or no bean damaged and low weight loss of bean at certain plant powders were observed due to lack of insect survival stages such as insect infestation at the beginning of the experiment, eggs and neonate larvae against VOCs.…”
Section: Insect Biology Testmentioning
confidence: 99%